Religious commitment in scriptural reasoning: a critical engagement with Gavin D'Costa's “Catholics Reading the Scripture of Other Religions” - Sarisky, D (Wiley, 2019)
The essay considers the objection that Scriptural Reasoning does not actually bring particular religious points of view into discussion, but rather suppresses traditions by the way it is organized. The article contends that, while Scriptural Reasoning as a whole is not entirely determined by a defining statement from any single religious tradition, any given participant can and is encouraged to bring the fullness of their commitment to discussion, and even overarching accounts of Scriptural Reasoning may well deploy the resources of a tradition. The essay closes by testing Scriptural Reasoning against criteria for being religious, concluding that it allows religious commitment to function in every respect that matters, given that it allows multiple traditions to have a say in how the practice is configured.